3 - ‘Dependency among Kautilya’s Three Major Ideas: Upaya, Sadgunya, and Prakrti’ - Krishna Kumar Saha (Identity, Culture and Politics, 2018)
In this current study, I will develop three different values for 7 Prakrti. The status of the Prakrti will be valued by ‘0’ for ‘stable’ and ‘-1’ is ‘decline’ and ‘1’ is ‘advancement’ position respectively. Then I will determine the other positions of Upaya and Sadgunya by evaluating those values from Prakrti.